Political Intersectionality: Tackling Inequalities in Public Policies in Scandinavia - Anette Borchorst (The Royal Danish Library, 2010)
Political Intersectionality: Tackling Inequalities in Public Policies in Scandinavia An analytical approach to political intersectionality has not been in the foreground of the intersectionality paradigm during its first phase. It may, however, generate new insights, both for the intersectionality tradition and for the study of policies that are aimed at influencing social differentiations. The article explores the theoretical background of political intersectionality with a focus on public policies, which relates to a macro level of political intersectionality. A central issue is whether policies are based on a unitary, a multiple or an intersectional policy logic. Moreover, the questions are whether and intersectional approach is inclusive or if it exclusively can stand alone, and, further, whether it is always positive. This is addressed empirically in relation to gender and integrations policies in the three Scandinavian countries.